Epileptogenic malformations of cortical development: when evolution goes awry - Tumienė, Birutė; Utkus, Algirdas (Acta medica Lituanica, 2014)
Background. Since the time of its origin in a mammalian ancestor, perhaps 250 million years ago, the neocortex has undergone expansion in both relative and absolute size. The complexity of the brain in vertebrates is proportional to the elaboration of the mechanisms controlling cortical development. Malformations of cortical development (MCD) are classified into three major groups that recapitulate the main developmental steps: cell proliferation, neuronal migration, or postmigrational cortical organization and connectivity. The main clinical manifestations of MCDs are epilepsy and / or intellectual disability. Seizures are the most common clinical feature, at least 75% of patients with MCDs will have epilepsy. Recent advances in neuroimaging techniques and revolutionary achievements in molecular biology led to an explosive increase in our knowledge of cerebral cortex development and malformations of cortical development (MCD). So far, more than 100 genes were associated with one or more types of MCD. However, the genetic cause still remains unidentified in the majority of cases. Conclusions. Investigations of human malformations of cortical development as of a model of impaired neurodevelopment gave a lot of important insights into normal and abnormal brain development processes and practical benefits to MCD patients and their families. Recent achievements in genetic technologies led to a real explosion in such knowledge and are expected to yield even more additional information in the near future.
Keywords: malformation of cortical development; neuronal migration; evolution